ANALISIS PENGGUNAAN PENDEKATAN SOCIO-SCIENTIFIC ISSUES (SSI) DI PERGURUAN TINGGI - Diah Nugraheni; Dyah Setya Winarni; Khasanah Khasanah (Dharmas Education Journal (DE_Journal), 2022)
Science learning is expected to be able to achieve the learning objectives, namely meaningful learning supported by increased understanding of scientific literacy in students. For that we need a learning pattern that connects the ability to process information obtained with scientific concepts and can be implemented in everyday life. The information obtained is of course not only understanding but also problems that exist in the environment that require solving a situation that creates a dilemma between existing facts and the concept of science as the basis of science. For that we need the right learning approach to assist in solving problems that exist in the environment, one of which is the socio-scientific issue (SSI) learning approach. This study uses a survey with data analyzed descriptively qualitatively. The subjects of the study were 23 science education lecturers with a minimum teaching qualification of 2 years. The results obtained are that 74% of science education lecturers are familiar with SSI, and 26% of science education lecturers are not familiar with SSI. SSI is more appropriate to be used in environmental learning activities as the implementation of all science concepts. The conclusion of this study is that the learning carried out by science education lecturers has not used the socio-scientific issue (SSI) approach in science learning.